The labor market in Latin America at the time of the COVID-19 pandemic: impacts, responses and perspectives - Maurizio, Roxana; Bertranou, Fabio (Gaceta Médica de Caracas, 2020)
Latin America is experiencing an unprecedented crisis in its labor markets because of the COVID-19 pandemic. This is reflected in a drastic contraction of employment, hours worked, and income. The outlook is even more worrying when considering that these impacts have been unequal, and that the path to recovery, which is slowly emerging in the region, could be accompanied by a widening of labor and income gaps across different population groups. América Latina experimenta una crisis sin precedentes en sus mercados de trabajo como consecuencia del COVID-19. Esto se refleja en una drástica contracción del empleo, de las horas trabajadas y de los ingresos. El panorama resulta aún más preocupante al considerar que dichos impactos han sido desiguales, y que el lento sendero de recuperación podría ir acompañado de una amplificación de brechas laborales y de ingresos entre los diferentes grupos de población.